If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(7m + 4) = 20 + -5m Reorder the terms: -3(4 + 7m) = 20 + -5m (4 * -3 + 7m * -3) = 20 + -5m (-12 + -21m) = 20 + -5m Solving -12 + -21m = 20 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. -12 + -21m + 5m = 20 + -5m + 5m Combine like terms: -21m + 5m = -16m -12 + -16m = 20 + -5m + 5m Combine like terms: -5m + 5m = 0 -12 + -16m = 20 + 0 -12 + -16m = 20 Add '12' to each side of the equation. -12 + 12 + -16m = 20 + 12 Combine like terms: -12 + 12 = 0 0 + -16m = 20 + 12 -16m = 20 + 12 Combine like terms: 20 + 12 = 32 -16m = 32 Divide each side by '-16'. m = -2 Simplifying m = -2
| 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 | | 6(1-4y)-5y=-8(3+4y) | | 6x+9y=2 | | 2k-4=12 | | 4-3x=-3+4x | | 3.5x+1.25= | | -25k=-150 | | 82=-65-x |